Sustainable flavor, healthy future: toward a green transition of the UPV in the food sector - Rebeca López López; María Belén Picó Sirvent; Débora Domingo-Calabuig; Javier Martínez-Monzó; Purificación García-Segovia (Frontiers in Psychology)
IntroductionDue to the current climatic situation of the planet and the increase in concern for the environment, the Universitat Politècnica de València (UPV) aims to be a model for the university community in terms of the preservation of the ecosystem and prevention of the environmental impact caused by daily tasks; thus, aligning itself with the goals of the 2030 Agenda. For this reason, a project has been launched to carry out the green transformation of the UPV toward a university that prioritizes sustainability in all its areas.MethodsAs part of this project, a survey was conducted using anonymous online questionnaires for the student population and employees. The study aimed to gauge the perception of sustainability and campus food supply and included items related to waste management and public awareness. A total of 800 students and 100 employees from the three UPV campuses (Vera, Alcoy, and Gandía) participated, ranging from 17 to 66 years old.ResultsAfter the statistical analysis of the results, significant differences were identified in most of the questions of the different thematic blocks and, in some cases, in terms of gender and age group. In general, good knowledge about sustainability was observed, although participation in initiatives organized by the university was low in both population groups. On the other hand, as the age of the participants increased, a greater adoption of sustainable behaviors was observed, especially in buying and recycling habits. Regarding the food supply on university campuses, the need to improve it to promote healthier and more sustainable options is highlighted. This work investigates ways to improve the menu choices offered in university settings to promote healthier and more sustainable habits. Additionally, the study aims to identify potential obstacles within the university environment that may hinder these efforts, raise awareness, and encourage more environmentally friendly behaviors.DiscussionThe proposed improvements include: (i) increasing the variety of plant-based options, (ii) sourcing food locally to reduce its carbon footprint, and (iii) implementing a waste management system that encourages recycling.